Nowożytna „fortalicja” w Gorzkowicach, gmina loco, województwo piotrkowskie - Andrzejewski, Aleksander; Pietrzak, Janusz (Acta Universitatis Lodziensis. Folia Archaeologica, 1997)
Site I in Gorzkowie, Piotrków voivodeship, the so-called fortalicium is situated on the south-east of the village, on the left bank of the river Prutka. The object was formed by digging a 7 m high and 10 m deep moat which cut off a natural hummock spreading out along the river from the rest of terrain. As a result of this action a rectangle of 110 m x 70 m was shaped. In the north of the object there is a hollow, 40 m wide wedging it into 30 m. Altogether there were 29 excavations within the area of 350 m2 and the cubature of 300 m3 was digged out. Moreover 100 bores (sorted out in seven strings) were made by a geological drill. The excavations situated in a plateau of the object resulted in a negative out-come i.e. layers associated with the use of it were not found. In the excavations located in the hollow (in the north of the object) relics of wall foundations and their negatives were revealed. The remains of a building of 27 m x 12,5 m were uncovered. It had presumably a military function. Little of archeological materials was found and the overwhelming majority comes from the modern period or even present times. The object in Gorzkowice is regarded as an unfinished plan of the so-called palazzo in fortezza which was being built in the first half of 17th century and was soon interrupted by the Swedish wars. Therefore the foundation that had been planed there were never realized. Moreover, the masonry object which had already been built fell into pieces.